Conhecimento e opinião da população sobre o transplante e a doação dos tecidos da face - Rossetto, Daniela Cristina Pavan [UNESP] (2013)
The face transplantation is a surgical procedure in which facial structures are transplanted from one person to another. It's a complex procedure on a medical point of view, moral and psychological, therefore provides many benefits in terms of improving aesthetic function and social integration. To evaluate the knowledge and opinion of the population about the donation and transplantation of facial tissues. From August 2011 to October 2012 a questionnaire was administered to 430 people, randomly selected, with twenty-one years of age or older, systematically collected in all regions (north, south, center , east and west) of the city of Botucatu, state of São Paulo. The study of the objective responses of all participants in the different issues was accomplished by establishing a frequential distribution data presented using tables and graphs and analyzed by chi square (à) for a sample. The analysis of the responses were discussed at the 5% level of significance and considered significant when the p value was <0.05, showing that the distribution is not uniform, but uniformly distributed of the classes. The answers to the descriptive questions were analyzed by reading them and preparation of a summary with analysis by region. Of the participants, 65.8% did not have any knowledge about facial tissue donation, 90.1% knows that face transplantation is indicated in cases of facial deformities, 51.7% are able to donate tissues of the face, 67.7% are not aware how their families would react against its manifestation in life to give tissues of the face, 84% have no knowledge about the implications on the funeral ceremonies. Of all participants, 359 would accept to live with other face if necessary and 375 would support any family members in being a donor. The population showed a limited knowledge about the implications on the donation and transplantation of face tissues, but would accept to live with if necessary and support any family members ...